Inclusion in Uncertain Times: Changes in Practices, Perceptions, and Attitudes around Accessibility and Inclusive Practice in Higher Education - Kate Lister; Victoria K. Pearson; Tim Coughlan; Felipe Tessarolo (Education Sciences, 2022)
Accessibility, inclusive teaching, and student support are multi-faceted; they are dependent on wider institutional factors, such as leadership, resource, systems, and culture. To be truly inclusive requires a whole institution approach, with voices, perspectives, and stakeholder buy-in sought from across the institution. This can be extremely challenging because these can be sensitive to myriad institutional, sector, and societal changes that can influence working practices, resource management, and capacity. In this paper, we analyse responses from three iterations of a biennial staff survey conducted in 2017, 2019, and 2021 at the Open University (OU), capturing views on accessibility and inclusion before and during the COVID-19 pandemic and other challenging circumstances. These responses, from tutors, module and programme teams, educational technologists, library staff, and student support teams, reveal crucial insight into the (in)accessibility of support and practice across the institution, as well as insight into staff skills, attitudes, and knowledge around accessibility, and the fitness for purpose of the systems and structures in place. In this analysis, we explore how staff practices and perceptions change over time; identify the themes that remain constant over time, despite global circumstances; and explore how these themes can inform a whole-institution approach to accessibility and inclusion.